Correction: Mental Fatigue Might be Not So Bad for Exercise Performance After All: A Systematic Review and Bias-Sensitive Meta-Analysis. Issue 1 (19th July 2021) - Holgado, Darías; Sanabria, Daniel; Perales, José C.; Vadillo, Miguel A.
This article details a correction to: Holgado, D., Sanabria, D., Perales, J. C., & Vadillo, M. A. (2020 ). Mental Fatigue Might Be Not So Bad for Exercise Performance After All: A Systematic Review and Bias-Sensitive Meta-Analysis. Journal of Cognition, 3(1), 38. DOI: https://doi.org/10.5334/joc.126